The Garden Buildings Manual - Lush, Tony (Sparkford, Yeovil : Haynes Publishing, 2007)
Containing clear colour photographs and detailed plans and diagrams, this attractively presented manual will show you how to design, plan and construct your own garden buildings, along with advice on the tools and materials needed for each job.
Includes index.
Keywords: Garden structures -- Design and construction -- Amateurs' manuals; House and Home